AKTIVITAS XILANASE DARI Bacillus altitudinis YANG DIPRODUKSI DENGAN VARIASI WAKTU INKUBASI DAN KONDISI PENGUJIAN pH NETRAL DAN ALKALIN - Sugiyono Saputra; Alida Hanoum; Mulyadi Mulyadi; Achmad Dinoto (BERITA BIOLOGI, 2022)
Xylanases are hydrolytic enzymes which randomly cleave the β-1,4 backbone of the complex plant cell wall polysaccharide xylan. In this study, we investigate the extracellular enzyme activity of three strains of Bacillus altitudinis which produced with various production times in neutral (pH 7) and alkaline (pH 9) conditions. Crude enzyme was obtained from inoculated production medium containing 2% w/v xylan after six different time of incubations, including 0, 24, 48, 72, 96 and 120 hours.  The stationary phase of those three strains was observed after 72 hours of incubation, in accordance with significant increase of xylanase activity both in neutral and alkaline assay conditions. However, the highest of xylanase activity was obtained after 92 hours of incubation, in all three bacterial strains tested. A thin layer chromatography (TLC) was performed, and it confirmed that the crudes enzymes was able to breakdown the xylan into oligosaccharides. A higher activity of xylanase was obtained in alkaline condition but not significantly different between those two conditions. B. altitudinis KBX08 has the highest xylanase activity (46.9U/ml) which produced after 96 hours of incubation, indicating their potential for further development as xylanase producer.